Callogobius williamsi, a new species of goby (Teleostei: Gobiidae) from the Marquesas Islands, with notes on the status of all nominal Callogobius species - Delventhal, Naomi R.; Mooi, Randall D. (Zootaxa, 2023)
Callogobius williamsi new species is described from the 32.9 mm SL holotype and 29 paratypes (6.9–32.5 mm SL) from the Marquesas Islands, South Pacific Ocean. Callogobius williamsi is distinguished from all other known Callogobius species by the following combination of characters: scales mostly cycloid, ctenoid scales, if present, restricted to the mid-lateral caudal peduncle, 23–26 (mode 25) scales in lateral series, preopercular papillae row (Row 20) absent, and the interorbital canal with pores B′, D, and F′ present. Callogobius williamsi belongs to a group of 23 nominal species (the hasseltii group) that are hypothesized to be monophyletic based on the shared presence of narrow and closely spaced dorsal processes of the cleithrum and an elongate caudal fin (greater than head length in specimens over 20 mm SL). Following the species description is a discussion of the status of all nominal species of Callogobius including a table that provides provisional status for all species correctly assigned to the genus.